Podmiot transseksualny w kulturze – oswajanie, tragizm, tekstualizacja - Kujawska-Kot, Anna (Przestrzenie Teorii, 2019)
The article presents the issue of the representation of a transsexual subject’s experience in various discourses. Pointing to the need for dialogical openness, the author proposes a transdiscursive perspective on transsexuality. By referring to the literary and historical discourses, the author proves that transsexual characters are constantly present in culture, but there is lack of textological reflection on this issue in studies on transsexual individuals. The author puts forward the thesis that these transsexual characters are searching for hypotexts in which they can find confirmation of their internal gender identity. As a result, during the process of transistion, they externalize themselves through intertextual bodywriting. On the one hand, they textualize themselves, but on the other hand, they create textual narrations about themselves. They want to exist socially throughout the text. The article is an attempt to open up theoretical reflections on transsexuality.